Equine Spindle Cell Carcinoma - Honório da Costa, Aline; Barbosa de Lucena, Ricardo; de Oliveira Barros, Isabella; Vieira de Sousa, Isabelle; Karoline Silva de Oliveira, Vanessa; Luana de Medeiros Silva, Jéssica; de Vasconcelos Azevedo, Marlon; Matos Souza Azevedo, Natália (Acta Scientiae Veterinariae, 2025)
Background: Spindle cell carcinoma (SpCC), a variant of squamous cell carcinoma (SCC), is a rare neoplasm that affects epithelial cells causing various cytomorphological changes, but its predisposition and diagnostic criteria remain poorly understood. The current report describes the interrelationship between clinical, radiographic, endoscopic, histopathological, and immunohistochemical findings of the first documented case of SpCC in a horse, as well as the successful procedures that resulted in the patient’s recovery. Case: A 10-year-old male horse of undefined breed, with brown coat color, weighing 360 kg, was referred for evaluation with a history of right nasal obstruction. The animal also had a history of “snoring sounds” whenever participating in competitions. The time of symptom onset was unknown since the owner reported that the horse was already ill at the time of acquisition. The right nasal lumen was occluded by a foul-smelling mass, with ulcerated areas, in addition to the presence of continuous bilateral mucopurulent discharge. The animal presented with inspiratory dyspnea and bilateral rubbing sounds. On percussion, the left frontal sinus and maxillary sinuses produced slightly solid sounds. Radiographic and endoscopic findings suggested nasal sinus inflammation, and we initiated a protocol of meloxicam (0.06 mg/kg), dipyrone [20 mg/kg], nebulized dexamethasone, camphor oil, and bromhexine hydrochloride diluted in saline, in addition to penicillin (4,000,000 IU, IV) every 48 h for 6 days and nasal lavage with iodine solution. The mass was excised surgically, and tissue samples were sent for histopathological examination. Grossly, the 2 fragments measured 14.1 x 8.5 x 1.2 cm and 15.0 x 8.5 x 1.2 cm, respectively, with a soft, yellowish, and gelatinous appearance with multifocal reddish areas. Microscopically, there was a myxoid matrix, binucleated cells, cell proliferation with moderate pleomorphism, eosinophilia, and indistinct cytoplasmic borders. Their nuclei were oval with speckled chromatin and prominent nucleoli. The cells showed positive immunostaining for vimentin and pan-cytokeratin AE1AE3. The patient was discharged from hospital 66 days after admission. Discussion: Considering that SCC tends to occur in response to genetic factors and sun exposure, it is possible that the same factors have predisposed the patient to the development of SpCC. Given the paucity of data on SpCC in animals, the patient’s diagnosis was only possible through an association of diagnostic methods with information obtained from reports in humans. Based solely on the predominantly spindle-shaped cell morphology and abundant mucinous matrix, the most likely diagnosis would be myxosarcoma. However, other findings were compatible with those most frequently described in reports of SpCC in humans, such as the absence of paraneoplastic syndrome, the local infiltration capacity of the tumor, and its yellowish gelatinous appearance, as well as the simultaneous immunostaining of vimentin and cytokeratin. This reinforced the reliability of the diagnosis of SpCC made in the horse. As recommended in these cases, the tumor was removed surgically. The patient has been followed up since surgery, with no signs of recurrence after the last reassessment. Keywords: neoplasm, ostectomy, horse, trepanning, immunohistochemistry. Título: Carcinoma de células fusiformes em equino Descritores: neoplasma, ostectomia, cavalo, trepanação, imunohistoquimica.